2012
DOI: 10.1111/j.1467-9701.2012.01478.x
|View full text |Cite
|
Sign up to set email alerts
|

FDI and Growth: What Cross‐country Industry Data Say

Abstract: The theoretical literature has discussed different channels through which foreign direct investments (FDI) promote host country’s economic growth, but empirical analyses have so far been rather inconclusive. In this paper, exploiting the information of a disaggregated data set on a panel of 14 manufacturing sectors for (a sample of) developed and developing countries over the period 1992–2004, we are able to provide robust evidence on the positive and statistically significant growth effect of FDI in recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 93 publications
(130 reference statements)
0
31
0
Order By: Relevance
“…Hence, since the set of capabilities expands cumulatively, stock data are more appropriate to measure the foreign impact on the local economy (Zhu & Jeon, 2007). Lastly, Nunnenkamp and Spatz (2004) point out that potential endogeneity biases are less likely for the stock than for the flow variable because foreign investment inflows are much more dependent on the present economic conditions in the host economy (see also Cipollina et al, 2012). 6 Nevertheless, we also estimate the model with FDI flows instead of stocks.…”
Section: Modelmentioning
confidence: 99%
“…Hence, since the set of capabilities expands cumulatively, stock data are more appropriate to measure the foreign impact on the local economy (Zhu & Jeon, 2007). Lastly, Nunnenkamp and Spatz (2004) point out that potential endogeneity biases are less likely for the stock than for the flow variable because foreign investment inflows are much more dependent on the present economic conditions in the host economy (see also Cipollina et al, 2012). 6 Nevertheless, we also estimate the model with FDI flows instead of stocks.…”
Section: Modelmentioning
confidence: 99%
“…Numerous recent studies have proven the different impacts of F.D.I. on the productivity of each sector (Alfaro, 2003;Cipollina, Giovannetti, Pietrovito, & Pozzolo, 2012;Tondl & Fornero, 2010).…”
Section: Review Of Literaturementioning
confidence: 99%
“…13 Detailed corporate-level data on the largest M&As by inward investing firms for the period 2008-10 show more than half took place in the services sector, in particular in finance as well as in 11 This perhaps explains why the UAE Government undertook business reforms making it easier to obtain construction permits, as mentioned below in the discussion of the policy scene. 12 A number of studies have looked into positive spillover effects of foreign investments on domestic firms using firm and plant level data (Cipollina et al, 2012). Some studies have found no spillovers (Aitken and Harrison, 1999) and weak evidence of positive horizontal externalities (Alfaro and Rodriguez-Clare, 2004), while other firm and plant-level studies have found strong evidence of knowledge spillovers (Branstetter, 2006;Haskel et al, 2006;and Keller and Yeaple, 2009 (Table 6).…”
Section: Fdi Mode and Corporate Playersmentioning
confidence: 99%
“…9 A number of studies have found positive effect of FDI on growth in different countries. Cipollina et al (2012) cite studies which find positive effect of FDI on growth using sector data: Caves (1974) for Australia, Globerman (1979) for Canada, Bl€ omstrom and Persson (1983), Bl€ omstrom and Wolff (1994) for Mexico, Sj€ oholm (1999) for Indonesia, Haskel et al (2006) for the UK and Keller and Yeaple (2009) for the US. the share of real estate in the stock of FDI was the most volatile among the different sectors.…”
mentioning
confidence: 99%